2019
DOI: 10.1136/vetreccr-2018-000792
|View full text |Cite
|
Sign up to set email alerts
|

Rhinitis following intraoperative gastro‐oesophageal reflux in a dog

Abstract: A four-month-old, male dog underwent surgical repair of femoral and pelvic fracture. The dog was premedicated with acepromazine combined with morphine; anaesthesia was induced with propofol to effect and maintained with isoflurane in 100 per cent oxygen. One hour after induction the dog regurgitated and gastric contents emerged through the nares. At the end of the surgery rhinoscopy and oesophagoscopy were performed. The oesophageal mucosa was apparently normal, while posterior and retrograde rhinoscopy reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The incidence of gastroesophageal reflux in dogs under general anaesthesia (GA) is reported to vary widely from 5% (Savvas et al 2016) to 87.5% (Lambertini et al 2020). After an episode of reflux, dogs can potentially suffer from oesophageal stricture, oesophagitis (Melendez et al 1998, Leib et al 2001, Wilson & Walshaw 2004) and/or aspiration pneumonia (Melendez et al 1998, Wilson & Walshaw 2004, Flouraki et al 2020) with a reported mortality rate for oesophageal stricture ranging from 12% to 23% (Melendez et al 1998, Leib et al 2001, Wilson & Walshaw 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of gastroesophageal reflux in dogs under general anaesthesia (GA) is reported to vary widely from 5% (Savvas et al 2016) to 87.5% (Lambertini et al 2020). After an episode of reflux, dogs can potentially suffer from oesophageal stricture, oesophagitis (Melendez et al 1998, Leib et al 2001, Wilson & Walshaw 2004) and/or aspiration pneumonia (Melendez et al 1998, Wilson & Walshaw 2004, Flouraki et al 2020) with a reported mortality rate for oesophageal stricture ranging from 12% to 23% (Melendez et al 1998, Leib et al 2001, Wilson & Walshaw 2004).…”
Section: Introductionmentioning
confidence: 99%
“…1998, Wilson & Walshaw 2004, Flouraki et al . 2020) with a reported mortality rate for oesophageal stricture ranging from 12% to 23% (Melendez et al . 1998, Leib et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although GOR is usually not observed or routinely monitored during anesthesia the consequences may be detrimental. In veterinary medicine, it has been reported that GOR during anesthesia may result in esophagitis, esophageal stenosis, esophageal rapture, rhinitis or aspiration pneumonia, which may even lead to death or euthanasia of the patient [ 7 , 8 , 9 , 10 , 11 , 12 ]. GOR during anesthesia is influenced by many factors included preoperative fasting, type of food administered, premedication sedatives, opioids, anesthetics, type of surgery, recumbency, duration of anesthesia, age [ 2 , 3 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%